3D Printed Enzyme‐Functionalized Scaffold Facilitates Diabetic Bone Regeneration. (9th March 2021) - Yang, Chen; Zheng, Zhiwei; Younis, Muhammad Rizwan; Dong, Chenle; Chen, Yahong; Lei, Shan; Zhang, Dong‐Yang; Wu, Jiayingzi; Wu, Xueqing; Lin, Jing; Wang, Xiansong; Huang, Peng
Abstract: Patients with diabetes mellitus (DM) suffer from a high risk of fractures and poor bone healing ability. Surprisingly, no effective therapy is available to treat diabetic bone defect in clinic. Here, a 3D printed enzyme‐functionalized scaffold with multiple bioactivities including osteogenesis, angiogenesis, and anti‐inflammation in diabetic conditions is proposed. The as‐prepared multifunctional scaffold is constituted with alginate, glucose oxidase (GOx), and catalase‐assisted biomineralized calcium phosphate nanosheets (CaP@CAT NSs). The GOx inside scaffolds can alleviate the hyperglycemia environment by catalyzing glucose and oxygen into gluconic acid and hydrogen peroxide (H2 O2 ). Both the generated H2 O2 as well as the overproduced H2 O2 in DM can be scavenged by CaP@CAT NSs, while the initiated hypoxic microenvironment stimulates neovascularization. Moreover, the incorporation of CaP@CAT NSs not only enhance the mechanical property of the scaffolds, but also facilitate bone regeneration by the degraded Ca 2+ and PO4 3− ions. The remarkable in vitro and in vivo outcomes demonstrate that enzymes functionalized scaffolds can be an effective strategy for enhancing bone tissue regeneration in diabetic conditions, underpinning the potential of multifunctional scaffolds for diabetic bone regeneration. Abstract : A 3D printed enzyme‐functionalized scaffold based on glucose oxidase (GOx) and catalase (CAT)‐assisted biomineralized calcium phosphate (CaP) nanosheets (CaP@CAT NSs) is prepared. The hyperglycemia and inflammation environment can be alleviated by the catalysis of GOx and CaP@CAT NSs. Meanwhile, the initiated hypoxia can stimulate angiogenesis and the degraded Ca 2+ and PO4 3− ions can enhance osteogenesis, thus facilitating diabetic bone regeneration.